Novel Approach to Repairing a Traumatic Aortic Arch Pseudoaneurysm Following a Fall - Hussain, Azhar; Youssefi, Pouya; Soppa, Gopal; Jahangiri, Marjan (AORTA, 2019)
Traumatic pseudoaneurysms of the aortic arch are often treated with surgical repair regardless of the lesion size or age. The authors report a simple, less invasive surgical repair in a patient who sustained blunt aortic injury following a fall.
Keywords: aorta; pseudoaneurysm; traumatic aneurysm